Perancangan Interior Galeri Sneakers dan Workshop Bagi Komunitas Sneakers di Surabaya - Vincent Hartanto; Grace Mulyono (Intra, 2017)
Sneakers are the type of shoes with flexible soles made of rubber or synthetic material and the top is made of leather or canvas. However, as the development of many of today sneakers are made also of suede and nylon. Sneakers originally taken from the word in the English language, the 'sneak' which means skirmishers. Initially sneakers are sports shoes and other shoes used for sports. Sneakers history itself first appeared in the 1800s under the name 'plimsolls', no name sneakers that time. In 1892 a rubber shoe company, Goodyear, creating a new shoe-making process by mixing the base material of rubber with canvas. The result Keds shoes branded on the market. In 1908, Converse enliven the footwear business. Companies belonging to this M.Converse Marquis directly into a booming with the emergence in many games of basketball in America. Not surprisingly sneakers from Converse and became American Icon. In 1920 a man named Adi Dassler, sportswear business owners from Germany shortly after making handmade training shoes. The company was then known as Adidas. And seiringnya changing times many companies that stand to produce sneakers such as Nike, New Balance, Vans, Asics, Puma, Reebok, etc. Since 1990 until now enthusiast sneakers become more and more and grow, because sneakers at this time become something special for the fans. Sneakers are not only sold to be used but also used as a collector's item. As with cars, there is also a rare sneakers limited edition and only sold a few pieces in the world. Sneakers any former or condition if it would have limited the goods are sought after by collectors in the world. Sneakers now become mandatory for youth fashion. Not only young people, old people were also quite a few are crazy about sneakers.